2018
DOI: 10.1111/cura.12257
|View full text |Cite
|
Sign up to set email alerts
|

Empathy for Animals: A Review of the Existing Literature

Abstract: Empathy is often studied as it relates to humans. However, there is a increasing interest in its relationship, development and impact with non‐human animals. This interest is often driven by a curiosity in empathy's role as an internal motivator for pro‐environmental behavior change. As with many internal affective responses, the link is not always directly clear but growing evidence suggests that empathy towards others can influence the likelihood of pro‐environmental behaviors as they relate to individual an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(89 citation statements)
references
References 70 publications
2
86
0
1
Order By: Relevance
“…Future studies should describe in detail how experiences in nature take place, including the meteorological conditions as well as the natural elements participants might encounter. The possible positive impact of direct and visual contact with non-human animals on people’s pro-environmentalism also needs further consideration [see Young et al (2018) for a review]. Finally, the word nature can have different meanings for people from different cultures (Wohlwill, 1983; Collado et al, 2016; Profice, 2018) and as such the definition of experiences in nature should take into account participants’ cultural background.…”
Section: Future Researchmentioning
confidence: 99%
“…Future studies should describe in detail how experiences in nature take place, including the meteorological conditions as well as the natural elements participants might encounter. The possible positive impact of direct and visual contact with non-human animals on people’s pro-environmentalism also needs further consideration [see Young et al (2018) for a review]. Finally, the word nature can have different meanings for people from different cultures (Wohlwill, 1983; Collado et al, 2016; Profice, 2018) and as such the definition of experiences in nature should take into account participants’ cultural background.…”
Section: Future Researchmentioning
confidence: 99%
“…According to the results, the most inspiring part of the day was a presentation about helping students develop an environmental ethic through building empathy for animals [28], age-appropriate environmental topics, and taking action. It included activities that allowed PSTs to discover their own connections to animals and discuss how they can help their students develop empathy for animals, starting with those with which they interact.…”
Section: Empathymentioning
confidence: 99%
“…Studies on empathy have generally followed a two-dimensional perspective: The cognitive perspective—mental perspective taking—[88,97,98], and the emotional perspective—the vicarious sharing of emotion—[87,99,100]. Recent studies have found that “both cognition and affect are important, but more research is needed to determine how they work together” [101].…”
Section: Introductionmentioning
confidence: 99%